Narrative Approaches as a Supplementary Source of Knowledge on Marginalized Groups - Follesø, Reidun; Hanssen, Jorid Krane (Qualitative Sociology Review, 2010)
This article reflects upon two different research projects that involve narratives from youth in care and youth growing up in families with gay and lesbian parents. We argue that these narrative approaches may offer a supplementary source of knowledge on marginalized groups that often seem hard to reach. The first method involves the participant and researcher collaborating to convert an oral narrative into a written one. In the second, the participants write an autobiographical narrative by themselves, covering themes specified by a researcher. The article is structured so that we first look at the processes of co-creating narratives and collecting autobiographical testimonies. We then introduce the two different methodological approaches by referring to empirical examples. Finally we reflect on the methodological and ethical challenges that occurred during this research.